Demonization and violence as tools of institutional power: the social cage of Thailand. (3rd July 2020) - Sripokangkul, Siwach; Crumpton, Charles David; Draper, John
ABSTRACT: Demonization has been used as tool for the maintenance of ruling regimes throughout history. Institutionalized, it becomes regime policy, exemplified in the extreme by the German Nazi regime's demonization of Jews. Dehumanized imagery is used to distinguish 'others', i.e. social, cultural, political, and/or economic out-groups, from 'normal' members of society and to support the power and control ambitions of those who hold or seek to hold dominant societal positions. Demonization is institutionalized through interaction among a variety of cultural carriers including religion, news media, and popular culture. It is used as an excuse for social exclusion and violence. It is most dangerous when it receives tacit acceptance or active support by central societal institutions, including government. The current article considers the processes and products of demonization in Thailand as it has appeared in national politics. Demonization has proven to be a strategic tool deployed by Thailand's 'social cage' to harm those who have sought political change and threaten its established institutional interests.